(3GdJYQja HGdeUWdM GdTQjas - (3CMeO Hf jMji Hf aVd Gddg GdbQTj GdYOhj GdYeQj, TgGH GdOjf,J (B749 (3g` s
(3ChdgG (B:s
(3Chdg aUd aj PcQ GdeUWdM GdeJYdb HGdEfTGA, eeG Cdag TjN gPg GdWQjbI TgGH GdOjf CMeO Hf aVd Gddg s
(3BNQgG (B:s
(3hjfJgj HJgfFI HYhOI ef GdML s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B204s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B420s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs